Individual and contextual determinants of malocclusion in 12-year-old schoolchildren in a Brazilian city - Lidia Moraes Ribeiro JORDÃO; Daniela Nobre VASCONCELOS; Rafael da Silveira MOREIRA; Maria do Carmo Matias FREIRE (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aim of this study was to describe malocclusion prevalence and its association with individual and contextual factors among Brazilian 12-year-old schoolchildren. This cross-sectional study included data from an oral health survey carried out in Goiânia, Brazil (n = 2,075), and data from the files of the local health authority. The data were collected through oral clinical examinations. The Dental Aesthetic Index (DAI) was used to assess occlusion. The presence of malocclusion (DAI > 25) was used as the dependent variable. The individual independent variables consisted of adolescents' sex and race and their mothers' level of schooling. The clinical variables were caries experience and presence of adverse periodontal condition (calculus and/or gingival bleeding). The contextual variables included type of school and the location of schools in the city's health districts. The Rao-Scott test and multilevel logistic regression were performed. The prevalence of malocclusion was 40.1%. In the final model, significantly higher rates of malocclusion were found among those who attended schools located in less affluent health districts and whose mothers had fewer years of education. Rates were also higher among those presenting calculus and/or gingival bleeding. Malocclusion demonstrated a high prevalence rate and the inequalities in its distribution were determined by individual and contextual factors.